Genetic Diversity and Virulences of Tungro Viruses on Rice in Indonesia - R. Heru Praptana; I Nyoman Widiarta (Iptek Tanaman Pangan, 2017)
Tungro virus disease is endemic in some rice-producing areas in Indonesia. The disease is caused by two different types of viruses, RTBV and RTSV, both are transmitted by green leafhopper. Genetic diversity and degree of virulences of the tungro viruses occur in the endemic areas of geographically diverse environments. Genetic diversity of the viruses do not correlate with their virulences. The virulence of tungro viruses was determined by specific interaction of the two types of tungro viruses, the vectors of the viruses and the resistance type of varieties. Informations on the genetic diversity and virulence of the tungro viruses from various endemic areas are needed to determine the disease control strategy and to apply more appropriate recommendation of resistant varieties. The information is also useful for disease epidemic monitoring and early detection of the presence of tungro viruses, and to be used as a basis in breeding for tungro virus resistant varieties, using conventional or genetic engineering techniques.